Towards a European constitution: fiscal federalism and the allocation of economic competences - Jürgen Stehn (Kiel Institute for World Economics (IfW), 2002)
The paper analyzes one important aspect of the constitutional debate: the allocation of econornie competences between the EU and the mernber states. It takes the theory of fiscal federalism as a starting point for an optimal allocation of economic competences. The main message of the theory is that a transfer of econornie competences from a lower to a higher political level always leads to a negligence of individual preferences and, therefore, can only be economically justified if national policies cause strong spillovers (externalities) to other jurisdictions. Based on this approach, the paper proposes an allocation of econornic conipetences that can serve as an overall. guideline for a European constitution.
Keywords: H77; F42; F15; H23; H11; 330; fiscal federalism; allocation of competences; European constitution; Wirtschaftspolitik; Policy-Mix; Finanzföderalismus; Spillover-Effekt; Föderalismus; Internalisierung externer Effekte; Verfassungsreform; Verfassungsökonomik; EU-Staaten